Small and medium scale business performance in Nigeria: Challenges faced from an intellectual capital perspective - Eniola, Anthony A.; Harry, Entebang; Sakariyau, Olalekan Busra (International Journal of Research Studies in Management, 2015)
The contribution of small and medium enterprises in a knowledge-based economic system is very salient for the economic growth and development of a developing nation like Nigeria. The competitiveness of the SMEs in a knowledge-based economy is the main purpose of this study. One of the most important component sources of sustainable competitive advantage in intellectual capital is the application of human capital. The paper will reviews the challenges that are confronting the small and medium enterprises (SMEs) performance in Nigeria from this position. The paper will increase the savoir faire about the present concern relating to Small and medium enterprises in Nigeria and human capital value creation. Small and medium scale business performance in Nigeria: Challenges faced from an intellectual capital perspective.